2022
DOI: 10.1111/issj.12317
|View full text |Cite
|
Sign up to set email alerts
|

Democracy and terrorism in Africa

Abstract: This study adds to the body of existing literature on the relationship between democracy and terrorism by investigating the impact of democracy on terrorism in 26 African countries. The study utilises a robust measure of democracy known as the varieties of democracy index which has been observed in literature to be more superior to conventional measures of democracy. A composite index of terrorism was derived from the number of terrorism incidents, the number of terrorist fatalities, and the number of terroris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Korotayev et al (2019) found that terrorist attack intensity decreased in more developed locations that promoted education (Korotayev et al 2019). More terrorism occurred in locations that restricted economic freedom (Gassebner and Luechinger, 2011), and locations in early stage democracy (Iheonu et al, 2021). Terrorists also tend to target locations with major international gateways such as ports because of the potential for massive disruptions in the supply chain (Young and Gordon, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Korotayev et al (2019) found that terrorist attack intensity decreased in more developed locations that promoted education (Korotayev et al 2019). More terrorism occurred in locations that restricted economic freedom (Gassebner and Luechinger, 2011), and locations in early stage democracy (Iheonu et al, 2021). Terrorists also tend to target locations with major international gateways such as ports because of the potential for massive disruptions in the supply chain (Young and Gordon, 2020).…”
Section: Introductionmentioning
confidence: 99%